Porous Ca3Co4O9 with enhanced thermoelectric properties derived from Sol–Gel synthesis. Issue 13 (October 2017) - Bittner, Michael; Helmich, Lailah; Nietschke, Frederik; Geppert, Benjamin; Oeckler, Oliver; Feldhoff, Armin
Abstract: Highly porous Ca3 Co4 O9 thermoelectric oxide ceramics for high-temperature application were fabricated by sol–gel synthesis and subsequent conventional sintering. Growth mechanism of misfit-layered Ca3 Co4 O9 phase, from sol–gel synthesis educts and upcoming intermediates, was characterized by in-situ X-ray diffraction, scanning electron microscopy and transmission electron microscopy investigations. The Ca3 Co4 O9 ceramic exhibits a relative density of 67.7%. Thermoelectric properties were measured from 373 K to 1073 K. At 1073 K a power factor of 2.46 μW cm −1  K −2, a very low heat conductivity of 0.63 W m −1  K −1 and entropy conductivity of 0.61 mW m −1  K −2 were achieved. The maintained figure of merit ZT of 0.4 from sol–gel synthesized Ca3 Co4 O9 is the highest obtained from conventional, non-doped Ca3 Co4 O9 . The high porosity and consequently reduced thermal conductivity leads to a high ZT value.